Implementation of HIV/AIDS policy in the Gauteng Department of Roads and Transport - Odame-Takyi, Kabane Tryphinah (My University, 2016)
HIV and AIDS impact severely on the capacity of the state, its skills base and the efficient use of public funds to render high quality services to the broad populace. Public sector institutions are under immense pressure to implement policies and programmes to mitigate the impact of HIV and AIDS in the workplace (Public Service Commission, 2006). In this context, the purpose of this research is to assess the implementation of HIV and AIDS policy in the Gauteng Department of Roads and Transport to determine if employees are benefiting from this policy. To accomplish this goal, the study employed qualitative interviews and observations to obtain the necessary data from DRT managers, programme officials and employees in June 2014. An examination of the data confirmed that efforts had been made to implement the HIV/AIDS policy in the DRT, although the scope and intensity of these initiatives varied across occupational levels. It was found that an internal policy on HIV and AIDS has been developed; some employees had been informed about the risks of HIV and AIDS; some line managers had been trained on HIV/AIDS management; health screening including HIV counseling and testing takes place regularly; employees have access to 24 hour counseling services; and some units had been supplied with educative messages including pamphlets and brochures. However, the findings also revealed gaps in the current implementation strategy, including limited communications, poor participation in campaigns, lack of leadership commitment, lack of resources and time constraints. In light of this, it was concluded that the current HIV/AIDS management strategy suffers from lack of capacity and coordination
A RESEARCH REPORT SUBMITTED TO THE WITS SCHOOL OF GOVERNANCE IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR A MASTER OF MANAGEMENT DEGREE IN PUBLIC AND DEVELOPMENT MANAGEMENT
Keywords: AIDS (Disease)--Government policy--South Africa.; HIV infections--Government policy--South Africa; Civil service--South Africa